Water from my heart : a novel - Martin, Charles, 1969- (New York : Center Street, 2016)
Charlie Finn had to grow up fast, living alone by age sixteen. Highly intelligent, he earned a life-changing scholarship to Harvard, where he learned how to survive and thrive on the outskirts of privileged society. That skill served him well in the cutthroat business world, as it does in more lucrative but dangerous ventures he now operates off the coast of Miami. Charlie tries to separate relationships from work. But when his choices produce devastating consequences, he sets out to right wrongs, traveling to Central America where he will meet those who have paid for his actions, including a woman and her young daughter. Will their fated encounter present Charlie with a way to seek the redemption he thought was impossible--and free his heart to love one woman as he never knew he could?"--
Includes reading guide.
106706
Keywords: Man-woman relationships; Businesspeople; Nicaragua; Love stories; Fiction; Romance fiction